Zinc and boron micronutrients application enhance sweet corn productivity - Hafith Furqoni; Erik Mulyana; Astryani Rosyad; Adrian Khairullah; Sofian Annas; Suwarto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Sweet corn (Zea mays L. var saccharata) is a valuable crop whose productivity depends not only on macronutrients but also on micronutrients such as zinc (Zn) and boron (B), which play essential roles in plant physiological processes. However, the effectiveness of foliar-applied micronutrients in sweet corn cultivation under tropical conditions remains insufficiently studied. This research aimed to evaluate the agronomic effectiveness of a micronutrient fertilizer containing Zn (5.46%) and B (3.59%) when combined with reference and reduced doses of NPK fertilizer. The experiment was conducted from February to May 2025 at the Sindangbarang Experimental Farm, IPB University. This experiment was conducted using a randomized complete block design with four treatments, namely control (no fertilizer), reference fertilizer, reference fertilizer + 1 dose of micronutrient fertilizer, and ¾ dose of reference fertilizer + 1 dose of micronutrient fertilizer, with six replications. Results showed that micronutrient application significantly enhanced vegetative growth and yield components compared to the control. The combination of reference NPK and one dose of micronutrient fertilizer produced the highest productivity, with a 78.8% increase over the control and a relative agronomic effectiveness (RAE) value of 114.5%, indicating a 1.14-fold improvement over the reference treatment. These findings suggest that integrating Zn and B into fertilization strategies can enhance sweet corn performance and support more efficient nutrient management in tropical agroecosystems. Keywords: crop yield improvement; foliar fertilization; micronutrient uptake; tropical field experiment; Zea mays physiology